Adjusting the starting dose of telaprevir according to renal function decreases adverse effects and affects the sustained virological response rate. Issue 1 (January 2015) - Morihara, Daisuke; Watanabe, Hiroshi; Takata, Kazuhide; Iwashita, Hideyuki; Tsuchiya, Naoaki; Kunimoto, Hideo; Kuno, Shizuka; Fukunaga, Atsushi; Yotsumoto, Kaoru; Tanaka, Takashi; Sakurai, Kunitoshi; Hirano, Genryu; et al.
Abstract : Background: Telaprevir (TVR) plays a major role in renal damage and anemia associated with TVR/pegylated interferon/ribavirin therapy for chronic hepatitis C. Adjusting the TVR starting dose may reduce these adverse effects. We aimed to determine whether adjusting the starting dose according to renal function reduces TVR-associated renal damage and anemia and affects the sustained virological response (SVR). Patients and methods: Our study included 112 patients infected with hepatitis C genotype 1 treated with pegylated interferon/ribavirin/TVR triple therapy. The TVR starting dose adjusted according to renal function was calculated as TVR/unadjusted estimated glomerular filtration rate (eGFR) ratio=TVR/(eGFR×body surface area/1.73). Results: A TVR/unadjusted eGFR ratio of 32 or greater was a predictor of renal impairment and anemia in multivariate analysis (odds ratio 12.09, P <0.001, and OR 4.14, P <0.001, respectively). Patients with a TVR/unadjusted eGFR ratio of 32 or greater developed significant renal impairment and anemia ( P <0.001 and P =0.002, respectively). SVR was significantly reduced in patients with a TVR/unadjusted eGFR ratio less than 23 versus 23 or greater (66.7 and 87.2%, respectively, P =0.045). SVR tended to increase stepwise [<23.0 (66.7%), ≥23 to <32 (84.8%), and ≥32 (89.6%), respectively]. The TVR/unadjusted eGFR ratio was correlated significantly with the serum TVR concentration ( r =0.541, P <0.001). Conclusion: Adjusting the TVR starting dose according to the TVR/unadjusted eGFR ratio decreased adverse effects and affected the SVR rate. The TVR starting dose should be adjusted by a TVR/unadjusted eGFR ratio of 23 or greater to less than 32 to safely achieve SVR.